A comparison design study of feedback modalities to support deep breathing whilst performing work tasks. - Cochrane, Karen Anne; Loke, Lian; Ahmadpour, Naseem; Schiphorst, Thecla; Campbell, Andrew; Núñez-Pacheco, Claudia (Work, 2021)
BACKGROUND: Deep breathing exercises are known to help decrease stress. Wearable and ambient computing can help initiate and support deep breathing exercises. Most studies have focused on a single sensory modality for providing feedback on the quality of breathing and other physiological data. OBJECTIVE: Our research compares different feedback modalities on an individual's experience and ability to perform breath-based techniques at work. METHODS: We designed three different interactive prototypes that used light, vibration and sound feedback modalities. We tested each prototype with 19 participants whilst they were performing typical work tasks in a naturalistic setting, followed by semi-structured interviews. RESULTS: We found that sound was the most successful feedback for the majority of participants, followed by vibration and ambient light. We developed an analytic tool, the Extended Cycle of Awareness, to facilitate understanding of the patterns of awareness and the flow of experience generated by participant interaction with prototype systems that provide feedback on the quality of breathing. Participants followed one of three different types of patterns: (1) ignoring the feedback; (2) not understanding the feedback and being overwhelmed by it; (3) successfully using the feedback to initiate deep breathing and reflect on the change in the quality of breathing. CONCLUSIONS: We offer a set of design recommendations for crafting interactive systems to support deep breathing at work, including personalization, designing for the cyclical process of attention and awareness, and designing for reflective practice.